Decreased blood product usage during extracorporeal life support with reduced circuit volumes. Issue 6 (16th March 2017) - Addison, Samuel D.; Buck, Marcia L.; Fang, Gary Y.; Gangemi, James J.; Kaufman, David A.
Abstract : BACKGROUND: Activation and consumption of platelets (PLT) and clotting factors along with hemolysis occurs when blood contacts the extracorporeal life support (ECLS) circuit and its components. STUDY DESIGN AND METHODS: The objective was to examine the effects of reducing ECLS circuit volume by decreasing tubing length and changing components on blood product usage in neonatal and pediatric patients. Blood product administration was analyzed in 40 consecutive patients who required ECLS for respiratory or cardiac failure before (PRE) and after (POST) changes in circuit design and components. RESULTS: The total circuit volume was reduced from 500 mL (PRE) to 275 mL (POST). In the POST group, total blood product volume usage was 58% lower compared to the PRE group (81 mL/kg/day vs. 191 mL/kg/day, p = 0.003), 65% lower for fresh‐frozen plasma (FFP; 15 mL/kg/day vs. 43 mL/kg/day, p = 0.001), and PLT volumes trended lower. In the subgroup of infants with respiratory or cardiac failure, there was a 55% reduction of a total blood product replacement (61 mL/kg/day vs. 136 mL/kg/day, p = 0.008), red blood cell (RBC) use was 61% lower (28 mL/kg/day vs. 71 mL/kg/day, p < 0.049), and there was a 73% reduction in FFP use (11 mL/kg/day vs. 41 mL/kg/day, p < 0.001). In the subgroup of postoperative infants, there was a 25% decrease in RBC use (86 mL/kg/day vs. 115 mL/kg/day, p = 0.03). CONCLUSION: Decreasing the ECLS circuit volume by reducing the tubing length and changing the components was associated with a significant reduction in blood product usage.